Smart Hydroponic System for Petroselinum Crispum Growth Monitoring with Nutrition Automation - N., Asha C; N., Sheetal; G., Divya G; R., Chandhini Kumari Arpitha M (IRO Journal on Sustainable Wireless Systems, 2025)
Hydroponics is a technique of growing plants using a water-based nutrient solution rather than soil and is well suited for small farmers, hobbyists, and commercial enterprises. It involves growing plants in a nutrient solution with or without a soilless substrate for physical support. A hydroponic system is an essential component of a plant factory. By using fewer resources, hydroponics is seen as a more sustainable option than traditional agriculture. This proposed study aims to provide a brief overview of hydroponic systems based on existing research and suggest an approach to enhance real-time monitoring of Parsley (Petroselinum crispum) plant growth. The research aims to develop an optimal environment for plant growth while minimizing resource wastage and maximizing yields by maintaining proper nutrient levels.